CORRELATION BETWEEN COMPUTER VISION SYNDROME AND UPPER LIMB DISORDERS AT WIDYA MANDALA CATHOLIC UNIVERSITY SURABAYA - Michael Christian Iskandar; Pauline Meryana; Paulus Alexander Supit (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: The world of technology that continues to develop, especially in computer, makes workers spend more time operating electronic devices. This can contribute to eye strain which is one of the most common symptoms of Computer Vision Syndrome (CVS). CVS may associated with musculoskeletal disorders, especially at upper extremities due to non-ergonomic body position, which can be referred to as Upper Limb Disorders (ULD). Therefore, CVS can affect the severity of ULD.Purpose: To explain correlation between CVS with ULD to students at Widya Mandala Catholic University Surabaya.Methods: Analytics observational was the type of this research and the research design was cross sectional study.Result: The groups of respondents who experienced CVS with the severity of ULD on a scale 0 (A): no pain; scale 1 (B): moderately painful; scale 2 (C): painful; scale 3 (D): very painful were found to be 34.3%, 25%, 2.3% and 0%. And the groups of respondents who did not experience CVS with the severity of ULD on a scale 0 (A), scale 1 (B), scale 2 (C), and scale 3 (D) were found to be 35.5%, 2.9%, 0%, and 0%. Results from Spearman test found that the p=0.000 so there’s a significant correlation between the two variables with a weak correlation coefficient (r=0,39).Conclussion: There was correlation between CVS and ULD with a weak correlation coefficient value in students at Widya Mandala Catholic University Surabaya